Individual Factors As Antecedents of Mobile Payment Usage - Radinal Setyadinsa; Muhammad Rifki Shihab; Yudho Sucahyo (Proceeding of the Electrical Engineering Computer Science and Informatics, 2018)
The aim of this research was to discover the stances of individual elements as antecedents of mobile payment usage. Data was gathered by distributing a questionnaire, which in latter steps was analyzed quantitatively. This research collected 90 samples, of whom represented users of a mobile payment service in Indonesia. The collected dataset was statistically analyzed, by employing partial least square structural equational modelling (PLS-SEM), aided with SmartPLS3.0. The results showed that two types of individual factors, namely individual difference and behavioral belief played significant roles in shaping users' intention to use mobile payments. Individual differences, consisting of mobile payment knowledge and compatibility significantly influenced perceived ease of use. Behavioral belief, such as trust, was shown to significantly influenced perceived usefulness. Finally, perceived ease of use and perceived usefulness concertedly affected mobile payment users' intention to use.